Comparison of clinicopathological characteristics between patients with occupational and non‐occupational intrahepatic cholangiocarcinoma. (3rd May 2016) - Hamano, Genya; Kubo, Shoji; Takemura, Shigekazu; Tanaka, Shogo; Shinkawa, Hiroji; Kinoshita, Masahiko; Ito, Tokuji; Yamamoto, Takatsugu; Wakasa, Kenichi; Shibata, Toshihiko
Abstract: Background: An outbreak of cholangiocarcinoma has been reported among workers of an offset color proof‐printing department at a printing company in Japan. In this study, we compared the clinicopathological findings of this type of intrahepatic cholangiocarcinoma (occupational ICC) and non‐occupational ICC. Methods: The clinical records of 51 patients with perihilar‐type ICC who underwent liver resection, including five patients with occupational ICC were retrospectively reviewed. The clinicopathological features were compared. Results: In the occupational group, the patients were significantly younger ( P <  0.01), while serum γ‐glutamyl transpeptidase activity and the proportions of patients with regional dilatation of the bile ducts without tumor‐induced obstruction were significantly higher ( P =  0.041 and P <  0.01, respectively); the indocyanine green retention rate at 15 min was significantly lower ( P =  0.020). On pathological examinations, precancerous or early cancerous lesions, such as biliary intraepithelial neoplasia and intraductal papillary neoplasm of the bile duct, were observed at various sites of the bile ducts in all occupational ICC patients; such lesions were observed in only six patients in the control group ( P <  0.01). Conclusions: The clinicopathological findings including age, liver function test results, diagnostic imaging findings, and pathological findings differed between the occupational and control groups. Abstract : Highlight Age, liver function test results, diagnostic imaging findings and pathological findings differed between occupational and non‐occupational intrahepatic cholangiocarcinoma. Hamano and colleagues suggest that these differences may be based on different carcinogenic processes between the conditions, and they stress the importance of regular health examinations for workers exposed to organic solvents.